Heavy Metal Concentrations In Bukit Merah Reservoir And Human Health Risk Due To Fish Consumption - Abdullah, Mohd Ilman Che (2022)
The freshwater ecosystem, such as Bukit Merah Reservoir (BMR), plays an important role ecologically and economically to the local population. The contamination of heavy metals in the surface sediment of BMR may cause adverse effects on the living biota in the reservoir and ultimately affect humans' health. This study's objectives were to evaluate the spatial distribution of heavy metals in the surface sediment of BMR and assess the ecological index assessment. This study also investigated the bioaccumulation of heavy metals in different parts of eight fish species found in the BMR and the health risk assessment for humans. A total of 30 surface sediment samples were collected and the physicochemical parameters of both water and surface sediments were also measured. The results showed that, the descending order of mean concentrations of heavy metals in the surface sediments of BMR was Fe > Mn > Pb > Zn > Cr > As > Cu > Ni. High accumulation of heavy metals was found in the southern part of the lake, where anthropogenic activities were predominant. In summary, the accumulation and enrichment of heavy metals in the surface sediment of BMR were due to anthropogenic factors such as plantations, logging, sand mining and discharges from fisherman piers.